MORPHOLOGICAL NATURALIZATION OF BORROWED LEXEMES IN URDU: A CORPUS-BASED STUDY (Contemporary Journal of Social Science Review, 2025)
This study aims to examine the morphological naturalization of borrowed English lexemes in contemporary Urdu and to identify whether this process constitutes a distinct pattern of word formation. Using a corpus-based and corpus-driven qualitative approach, data were collected from naturally occurring sources including public signage, educational texts, commercial labels, and everyday written discourse. The analysis focuses on how English-origin nouns such as ٹیبل، بک، اسکول، سسٹم، پنسل undergo systematic pluralization and grammatical integration through Urdu morphological patterns (e.g., ٹیبلیں، بکیں، اسکولوں). The findings reveal that these forms are no longer used as temporary borrowings or instances of code-mixing; rather, they function as fully integrated Urdu lexemes. The study argues that this process represents a distinct type of word formation—termed morphological naturalization—in which borrowed lexemes become structurally and cognitively embedded in the host language. This research is significant as it demonstrates that Urdu expands its lexicon not merely through borrowing, but through active grammatical restructuring, highlighting a dynamic and productive mechanism of lexical growth. The study is limited to written and publicly visible data and recommends further research using spoken corpora and larger datasets to extend the proposed framework.